1976
DOI: 10.1002/jhet.5570130323
|View full text |Cite
|
Sign up to set email alerts
|

Nmr spectroscopic studies on the tautomerism in tenuazonic acid analogs

Abstract: Nmr spectra of structural analogs of tenuazonic acid such as 3‐acetyltetramic acid, 3‐acetyltetronic acid, 3‐acetylthiotetronic acid and others were investigated for elucidation of the tautomeric structures. These compounds have completely enolized β,β′‐triketone systems, and the position of the nmr signals for the enolic proton shows that the strength of their intramolecular hydrogen‐bonding is weaker than those of acyclic β,β′‐triketones and six‐membered cyclic triketones. The assignment was made for nmr sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Consequently, a synergistic conformation constraint in the rigid b barrel structure of PyrI4 plays a crucial role in the conversion of 1 to 2, as multiple mutations of these residues, Q115A/Y85A, Q115A/ Y85A/E65A, Q115A/Y85A/E65A/E87A, Y85A/E65A/E87A, and Y85A/E65A/E87A/Y177A, showed additive effects toward the nearly complete inactivation of the enzyme ( Figure 4C). The acidic pocket of the b barrel provides an internal environment that may facilitate negative charge removal from the tetramate moiety of 1 (Yamaguchi et al, 1976) to lower the LUMO energy of dienophile, thereby allowing the Diels-Alder-like cyclization to proceed under the condition of physiological pH.…”
Section: Mutagenesis-based Bioassays Of the Enzymatic Activitymentioning
confidence: 99%
“…Consequently, a synergistic conformation constraint in the rigid b barrel structure of PyrI4 plays a crucial role in the conversion of 1 to 2, as multiple mutations of these residues, Q115A/Y85A, Q115A/ Y85A/E65A, Q115A/Y85A/E65A/E87A, Y85A/E65A/E87A, and Y85A/E65A/E87A/Y177A, showed additive effects toward the nearly complete inactivation of the enzyme ( Figure 4C). The acidic pocket of the b barrel provides an internal environment that may facilitate negative charge removal from the tetramate moiety of 1 (Yamaguchi et al, 1976) to lower the LUMO energy of dienophile, thereby allowing the Diels-Alder-like cyclization to proceed under the condition of physiological pH.…”
Section: Mutagenesis-based Bioassays Of the Enzymatic Activitymentioning
confidence: 99%
“…Tautomerism in tricarbonyl 3-acyltetramate systems is known to be complex and strongly dependent on the identity of the side chain acyl group [23]. 3-Acyl (X = CH 2 ) [10,2425], 3-carboxamide (X = NH) [8,10] and 3-alkoxycarbonyl (X = O) tetramic acids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The tautomerisation of 3-acyltetramic acids has been shown to be mainly affected by substitution on N(1) rather than the functionalities on the 3-acyl and C(5) positions. Thus, the dominant tautomer of N-unsubstituted and N -alkyltetramates is D, while N -acyltetramates exist as a mixture of external tautomers AB and D in approximately equal ratio [23]. By contrast, it was found that the tautomerisation of 3-carboxamides and 3-alkoxycarbonyls was not affected by substitution on N(1).…”
Section: Resultsmentioning
confidence: 99%
“…The results of As seen in Table Ma, the pupation was inhibited by some derivatives of 5-aryltetronic acid (13,15) and the benzylidene compound (21). The mortal effect was not observed in general, but compounds (4) and (8) showed it somewhat.…”
Section: Phytotoxic and Plant Regulatory Effectsmentioning
confidence: 98%